Metallicity and age of the stellar stream aound the disk galaxy NGC 5907 - Laine, Seppo K.; Martínez-Delgado, David (Arxiv, 2016)
Stellar streams have become central to studies of the interaction histories of nearby galaxies. To characterize the most prominent parts of the stellar stream around the well-known nearby (d = 17 Mpc) edge-on disk galaxy NGC 5907, we have obtained and analyzed new, deep gri Subaru/Suprime-Cam and 3.6 micron Spitzer/Infrared Array Camera (IRAC) observations. Combining the near-infrared 3.6 micron data with visible-light images allows us to use a long wavelength baseline to estimate the metallicity and age of the stellar population along a ~60 kpc long segment of the stream. We have fitted the stellar spectral energy distribution (SED) with a single-burst stellar population synthesis model and we use it to distinguish between the proposed satellite accretion and minor/major merger formation models of the stellar stream around this galaxy. We conclude that a massive minor merger (stellar mass ratio of at least 1:8) can best account for the metallicity of -0.3 inferred along the brightest parts of the stream.